Non-equilibrium wetting and capture of boron nitride nanotubes in molten aluminum during plasma spray. (1st July 2018) - Nautiyal, Pranjal; Zhang, Cheng; Boesl, Benjamin; Agarwal, Arvind
Abstract: Boron Nitride Nanotube (BNNT) is integrated into Aluminum (Al) matrix by plasma spray, involving non-equilibrium solidification. A wet chemistry approach is adopted to obtain Al-BNNT powder feedstock, which is plasma sprayed to form Al-BNNT composite. BNNTs survive the harsh and reactive conditions in plasma and are uniformly distributed in Al matrix. Trace amounts of AlN and AlB2 formed due to Al-BNNT reactions act as covalently bonded interfacial anchors. Rapid solidification enables efficient capture of BNNT in the molten Al due to viscous drag. BNNT improves the stiffness and hardness of the composite, acting as an effective mechanical reinforcement. Graphical abstract: Unlabelled Image